Pre-Service EFL Teacher Questioning Strategies During Practicum: A Case Study in Indonesia - Uun Muhaji (Faculty of Education and Teacher Training of UIN Palopo, 2025)
The role of teacher questioning in EFL classrooms is pivotal for fostering student engagement and language development. However, research on questioning strategies during school-based teaching practicum, a crucial phase in pre-service teacher education, remains scarce. To address this issue, a qualitative single-case study was conducted with one pre-service EFL teacher teaching 11th grade students in East Java, Indonesia. It explores the types of questions and questioning strategies employed by the teacher during teaching practicum. Data were collected through classroom observation and field notes. The findings reveal the use of five primary question types-referential, comprehension checks, display, confirmation checks, and clarification checks-alongside strategies such as rephrasing, repetition, decomposition, and simplification. These strategies were instrumental in promoting classroom interaction and supporting student comprehension. The study underscores the need for more targeted training in questioning techniques within teacher education programs to better equip pre-service teachers for effective classroom management and interaction.